Expert System of Anti-Diabetic Medicine Selection - Andi Hutami Endang (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2021)
The Prediction of World Health Organization (WHO) estimates that in 2030 the number of diabetics in Indonesia reached approximately 21.3 million people. Moreover, the development of medicine consumed by diabetics also varies. In this paper, we present a system that represents a diabetes expert into a knowledge based on the domain ontology. The early stage of the system is developing drugs ontology (including functions and contraindications) and patient ontology. Then, matching a weighted ontology will give drugs recommendations that are suitable with the patient's condition. The system is able to analyze diabetes symptoms to give drugs recommendations to the patient.